Bimetallic Two‐Dimensional Metal–Organic Frameworks for the Chemiresistive Detection of Carbon Monoxide. (22nd December 2021) - Aykanat, Aylin; Meng, Zheng; Stolz, Robert M.; Morrell, Colin T.; Mirica, Katherine A.
Abstract: This paper describes the demonstration of a series of heterobimetallic, isoreticular 2D conductive metal–organic frameworks (MOFs) with metallophthalocyanine (MPc, M=Co and Ni) units interconnected by Cu nodes towards low‐power chemiresistive sensing of ppm levels of carbon monoxide (CO). Devices achieve a sub‐part‐per‐million (ppm) limit of detection (LOD) of 0.53 ppm toward CO at a low driving voltage of 0.1 V. MPc‐based Cu‐linked MOFs can continuously detect CO at 50 ppm, the permissible exposure limit required by the Occupational Safety and Health Administration (OSHA), for multiple exposures, and realize CO detection in air and in humid environment. Diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS), density functional theory (DFT) calculations, and comparison experiments suggest the contribution of Cu nodes to CO binding and the essential role of MPc units in tuning and amplifying the sensing response. Abstract : A series of isorecticular and heterobimetallic two‐dimensional metal–organic frameworks achieves chemiresistive sensing of ppm concentrations of carbon monoxide at low power. Spectroscopic techniques and computational methods, along with comparative experiments, suggest the contribution of Cu nodes to CO binding and the essential role of metallophthalocyanine units in tuning and amplifying the sensing response.